The Ability in Writing Narrative Text by Using English Poetry at The Students of Al Asyariah Mandar - Andi Sudarmin Azis; Riki Bugis; Harziko Harziko (Hasanuddin University, 2022)
The students’ skill in writing narrative text is really needed to be improved. The implementation of English Poetry in the current research was aimed to improve the students’ writing narrative text of the students in the 2nd semester of the Islamic Economic Law study program, the faculty of Islamic Religion. The study applied quantitative method in light of pre and post-test of writing narrative text to both of control and experimental groups and distributing questionnaire to the experimental group to gain their perception upon the English poetry. A total of 34 students from control and experimental group were involved. Analytical scoring profile was used to measure the students’ writing narrative text.The result shows that students under the guidance of English poetry performed significantly better than students in control group with conventional way of teaching in which, the experimental group shows score of post-test was greater than control group by gaining mean score 78.25 and control group gained mean score 61.62. The analysis of questionnaire results reveals that the implementation of English poetry helped the students to be easier in writing narrative text. Most of the participants gave positive response to the use of English poetry in teaching writing narrative text.